Detection of enterovirus in the thyroid tissue of patients with graves' disease - Hammerstad, Sara Salehi; Tauriainen, Sisko; Hyöty, Heikki; Paulsen, Trond; Norheim, Ingrid; Dahl-Jørgensen, Knut (Journal of medical virology, 2013)
The etiology and pathogenesis of Graves' disease (GD) are still unknown, although it is thought that both genetic and environmental factors are important. Some indirect evidence implies that a viral infection may be a possible etiologic factor in autoimmunity. The main objective of this study was to examine direct evidence of the presence of enteroviruses (EVs) in the thyroid tissue of patients with GD. Thyroid tissue from 22 patients with newly diagnosed GD was obtained by core needle biopsy, while tissue from 24 patients with chronic GD and 24 control subjects without any autoimmune thyroid diseases was collected during neck surgery. Formalin‐fixed, paraffin‐embedded thyroid tissue samples were examined for the presence of enterovirus capsid protein using immunohistochemistry and for enterovirus RNA using in situ hybridization. Enterovirus capsid protein was detected in 17 (37%) patients and in 4 (17%) control subjects (P = 0.103). Enterovirus RNA was identified in thyroid tissue from nine (20%) patients, but in none of the control subjects (P = 0.016). Eight (90%) of the nine virus RNA positive patients were also positive for enterovirus protein. This is the first study to analyze thyroid tissue for EVs, including patients with untreated, newly diagnosed GD. The results suggest that EVs are more frequently present in thyroid tissue of patients than controls. Further studies are indicated to explore this association to find out if a low‐grade chronic enteroviral infection might be involved in the pathogenesis of GD and if this could offer new therapeutic and preventive opportunities. J. Med. Virol. 85:512–518, 2013. © 2012 Wiley Periodicals, Inc.